2020
DOI: 10.1109/access.2020.3012093
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Diagnosis Based on Extreme Learning Machine: A Review

Abstract: Computer-Aided Diagnosis (CAD) can improve the accuracy of diagnosis effectively, reduce the rate of misdiagnosis, and provide the support for the valid decision. In clinical applications, high requirements are often imposed on the execution speed and accuracy of CAD systems. The classifier is regarded as the core of the CAD system, that is, the performance of the classifier will have a decisive influence on the operating affection of the CAD system. Extreme Learning Machine (ELM) is a fast learning algorithm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Wang et al [24] reviewed the application of ELM in computer-aided diagnostics (CAD). The authors showed it is possible to apply ELM in the construction of CAD systems, so the perspective is broad and deserves further study.…”
Section: Elm Based On Metaheuristicsmentioning
confidence: 99%
“…Wang et al [24] reviewed the application of ELM in computer-aided diagnostics (CAD). The authors showed it is possible to apply ELM in the construction of CAD systems, so the perspective is broad and deserves further study.…”
Section: Elm Based On Metaheuristicsmentioning
confidence: 99%
“…This barrier was often mentioned (n = 48) as it requires appropriate data labelling supported by reliable annotation methods, which can be a very demanding process (need for trained staff to label or verify the data). This process was qualified as expensive, time-consuming, and subjective if not adequately performed [18,19,[23][24][25][26][27][28].…”
Section: B1 Datamentioning
confidence: 99%
“…2024, 14, 4005 2 of 20 the development of automated and precise dermatological lesion identification systems assumes paramount importance [5]. Computer-aided diagnosis (CAD) systems have made substantial strides in identifying and assessing various malignancies [6], spanning lung cancer [7], breast cancer [8], thyroid cancer [9], brain cancer [10], and liver cancer [11], among others. In the domain of skin cancer detection, CAD system implementation becomes indispensable, enhancing efficiency, curtailing time and costs, and compensating for the scarcity of dermatologists.…”
Section: Introductionmentioning
confidence: 99%